Jurist in Context: William Twining in Conversation with David Sugarman. (27th May 2020) - Twining, William; Sugarman, David
Abstract: This discussion derives from extended conversations between William Twining and David Sugarman in which William talks about his latest book, Jurist in Context: A Memoir ( JIC ) . JIC recounts the development of William's thoughts and writings, addressing topics central to his life and research. The dialogue conveys and extends the arguments on a selection of the topics addressed in the book, engaging with issues of particular interest to readers of this journal. Here, William adds a more personal commentary to his formal publications. The conversation facilitates reflection on issues such as law teaching and legal scholarship; the meaning, use, and limitations of 'law in context'; and the role and character of jurisprudence. It also offers a fascinating window on the development of, and the struggles surrounding, legal education and academic legal thought over the second half of the twentieth century and the early part of the twenty‐first.